Efecto de un trabajo con énfasis en solución de problemas retadores sobre las creencias acerca de las matemáticas de estudiantes de grado séptimo de educación secundaria de la IED Guillermo León Valencia - Escobar Sánchez, Rubén Esteban (Universidad Antonio Nariño, 2023)
The objective of this research was to describe the beliefs held by a group of seventh- grade students of the IED Guillermo León Valencia JT of basic secondary education about mathematics, and the impact of an experience with emphasis on solving challenging problems. This work is part of the research project "Contribution of training programs to the construction of epistemological beliefs of future mathematics teachers about mathematics, its teaching and learning " led by the Mathematics Education research group of the Universidad Antonio Nariño